A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Monoamine alterations in Alzheimer’s disease and their implications in comorbid neuropsychiatric symptoms - Shalini Saggu; Ava Bai; Mae Aida; Hasibur Rehman; Andrew Pless; Destany Ware; Ferenc Deak; Kai Jiao; Qin Wang (GeroScience, 2024)
Alzheimer’s disease (AD) is a devastating neurodegenerative disorder characterized by relentless cognitive decline and the emergence of profoundly disruptive neuropsychiatric symptoms. As the disease progresses, it unveils a formidable array of neuropsychiatric manifestations, including debilitating depression, anxiety, agitation, and distressing episodes of psychosis. The intricate web of the monoaminergic system, governed by serotonin, dopamine, and norepinephrine, significantly influences our mood, cognition, and behavior. Emerging evidence suggests that dysregulation and degeneration of this system occur early in AD, leading to notable alterations in these critical neurotransmitters’ levels, metabolism, and receptor function. However, how the degeneration of monoaminergic neurons and subsequent compensatory changes contribute to the presentation of neuropsychiatric symptoms observed in Alzheimer’s disease remains elusive. This review synthesizes current findings on monoamine alterations in AD and explores how these changes contribute to the neuropsychiatric symptomatology of the disease. By elucidating the biological underpinnings of AD-related psychiatric symptoms, we aim to underscore the complexity and inform innovative approaches for treating neuropsychiatric symptoms in AD. Graphical Abstract [created With Biorender.com]

A demographic survey of the Davis Strait polar bear subpopulation using physical and genetic capture‐recapture‐recovery sampling - Kylee D. Dunham; Markus G. Dyck; Jasmine V. Ware; Andrew E. Derocher; Eric V. Regehr; Harry L. Stern; Garry B. Stenson; David N. Koons (Marine Mammal Science, 2024)
Conducting assessments to understand the effects of changing environmental conditions on polar bear ( Ursus maritimus ) demography has become increasingly important to inform management and conservation. Here, we combined physical (2005–2007) and genetic (2017–2018) mark‐recapture with harvest recovery data (2005–2018) to estimate demographic rates of the Davis Strait polar bear subpopulation and examine the possible effects of climate, dynamic ice habitat, and prey resources on survival. Large sample sizes (e.g., 2,513 marked animals) allowed us to estimate temporal variation in annual survival rates using multistate mark‐recapture‐recovery models. We did not detect statistically significant effects of climate, ice habitat, and prey during the 13‐year study. Estimated total abundance in 2006 was 2,190, credible interval (CRI) [1,954, 2,454] and 1,944, CRI [1,593, 2,366] in 2018. Geometric mean population growth rate (0.99, 95% CRI [0.97, 1.01]) indicated the subpopulation may have declined slightly between 2006 and 2018. However, we did not detect a declining trend in survival or substantial change in reproductive metrics over this period. Given forecasts of major environmental change we emphasize the need to review monitoring programs for this subpopulation.

HB31 and HB21 regulate floral architecture through miRNA396/GRF modules in Arabidopsis - Young Koung Lee; Andrew Olson; Keunhwa Kim; Masaru Ohme-Takagi; Doreen Ware (Plant Biotechnology Reports, 2024)

SorghumBase: a web-based portal for sorghum genetic information and community advancement - Nicholas Gladman; Andrew Olson; Sharon Wei; Kapeel Chougule; Zhenyuan Lu; Marcela Tello-Ruiz; Ivar Meijs; Peter Van Buren; Yinping Jiao; Bo Wang; Vivek Kumar; Sunita Kumari; et al. (Planta, 2022)
Main conclusion SorghumBase provides a community portal that integrates genetic, genomic, and breeding resources for sorghum germplasm improvement. Abstract Public research and development in agriculture rely on proper data and resource sharing within stakeholder communities. For plant breeders, agronomists, molecular biologists, geneticists, and bioinformaticians, centralizing desirable data into a user-friendly hub for crop systems is essential for successful collaborations and breakthroughs in germplasm development. Here, we present the SorghumBase web portal ( https://www.sorghumbase.org ), a resource for the sorghum research community. SorghumBase hosts a wide range of sorghum genomic information in a modular framework, built with open-source software, to provide a sustainable platform. This initial release of SorghumBase includes: (1) five sorghum reference genome assemblies in a pan-genome browser; (2) genetic variant information for natural diversity panels and ethyl methanesulfonate (EMS)-induced mutant populations; (3) search interface and integrated views of various data types; (4) links supporting interconnectivity with other repositories including genebank, QTL, and gene expression databases; and (5) a content management system to support access to community news and training materials. SorghumBase offers sorghum investigators improved data collation and access that will facilitate the growth of a robust research community to support genomics-assisted breeding.

Effective coastal adaptation needs accurate hazard assessment: a case study in Port Resolution, Tanna Island Vanuatu - Gaelle Faivre; Rodger Tomlinson; Daniel Ware; Saeed Shaeri; Wade Hadwen; Andrew Buckwell; Brendan Mackey (Climatic Change, 2022)
Developing countries face risks from coastal hazards that are being amplified by climate change. The selection of effective adaptation interventions to manage these risks requires a sufficiently accurate assessment of the coastal hazard at a given location. Yet challenges remain in terms of understanding local coastal risks given the coarseness of global wave models and the paucity of locally scaled data in most developing countries, including Small Island Developing States (SIDS) like Vanuatu. This paper aims to examine the differences in hazard assessment and adaptation option selections arising from analyses using globally versus locally scaled data on coastal processes. As a case study, we focused on an eroding cliff face in Port Resolution on Tanna Island, Vanuatu, which is of concern to the local community and government authorities. The coastal process modeling revealed that the global wave data generated unrealistically high predictions of wave height within Port Resolution Bay. Expensive engineering adaptations designed to provide coastal protection were therefore likely to fail in preventing ongoing cliff erosion. In this case, the best adaptation solution involves changing land use to revegetate and help stabilize the cliff top. Our case study highlights the importance of accurate hazard assessment, especially in data-poor regions where the extrapolation of global datasets and models in the absence of local data can result in poor adaptation decision-making. Furthermore, the multidisciplinary approach applied here can be applied in other data-poor regions to strengthen analyses exploring the benefits of local adaptation interventions.

Assessing how ecosystem-based adaptations to climate change influence community wellbeing: a Vanuatu case study - Oz Sahin; Wade L. Hadwen; Andrew Buckwell; Chris Fleming; Dan Ware; James C.R. Smart; Allan Dan; Brendan Mackey (Regional Environmental Change, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Social benefit cost analysis of ecosystem-based climate change adaptations: a community-level case study in Tanna Island, Vanuatu - Andrew Buckwell; Dan Ware; Christopher Fleming; James C. R. Smart; Brendan Mackey; Johanna Nalau; Allan Dan (Climate and Development, 2020)

Using Historical Responses to Shoreline Change on Australia’s Gold Coast to Estimate Costs of Coastal Adaptation to Sea Level Rise - Daniel Ware; Andrew Buckwell; Rodger Tomlinson; Kerrie Foxwell-Norton; Neil Lazarow (Journal of Marine Science and Engineering, 2020)
Climate change impacts, sea level rise, and changes to the frequency and intensity of storms, in particular, are projected to increase the coastal land and assets exposed to coastal erosion. The selection of appropriate adaptation strategies requires an understanding of the costs and how such costs will vary by the magnitude and timing of climate change impacts. By drawing comparisons between past events and climate change projections, it is possible to use experience of the way societies have responded to changes to coastal erosion to inform the costs and selection of adaptation strategies at the coastal settlement scale. The experience of implementing a coastal protection strategy for the Gold Coast’s southern beaches between 1964 and 1999 is compiled into a database of the timing, units, and cost of coastal protection works. Records of the change to shoreline position and characteristics of local beaches are analysed through the Bruun model to determine the implied sea level rise at the time each of the projects was completed. Finally, an economic model updates the project costs for the point in the future based on the projected timing of sea level rise and calculates a net present value (NPV) for implementing a protection strategy, per km, of sandy beach shoreline against each of the four representative concentration pathways (RCP) of the Intergovernmental Panel on Climate Change (IPCC) to 2100. A key finding of our study is the significant step-up in expected costs of implementing coastal protection between RCP 2.6 and RCP 8.5—from $573,792/km to $1.7 million/km, or a factor of nearly 3, using a social discount rate of 3%. This step-up is by a factor of more than 6 at a social discount rate of 1%. This step-up in projected costs should be of particular interest to agencies responsible for funding and building coastal defences.

Projecting impacts of global climate and land‐use scenarios on plant biodiversity using compositional‐turnover modelling - Moreno Di Marco; Tom D. Harwood; Andrew J. Hoskins; Chris Ware; Samantha L. L. Hill; Simon Ferrier (Global Change Biology, 2019)
Nations have committed to ambitious conservation targets in response to accelerating rates of global biodiversity loss. Anticipating future impacts is essential to inform policy decisions for achieving these targets, but predictions need to be of sufficiently high spatial resolution to forecast the local effects of global change. As part of the intercomparison of biodiversity and ecosystem services models of the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services, we present a fine‐resolution assessment of trends in the persistence of global plant biodiversity. We coupled generalized dissimilarity models, fitted to >52 million records of >254 thousand plant species, with the species–area relationship, to estimate the effect of land‐use and climate change on global biodiversity persistence. We estimated that the number of plant species committed to extinction over the long term has increased by 60% globally between 1900 and 2015 (from ~10,000 to ~16,000). This number is projected to decrease slightly by 2050 under the most optimistic scenario of land‐use change and to substantially increase (to ~18,000) under the most pessimistic scenario. This means that, in the absence of climate change, scenarios of sustainable socio‐economic development can potentially bring extinction risk back to pre‐2000 levels. Alarmingly, under all scenarios, the additional impact from climate change might largely surpass that of land‐use change. In this case, the estimated number of species committed to extinction increases by 3.7–4.5 times compared to land‐use‐only projections. African regions (especially central and southern) are expected to suffer some of the highest impacts into the future, while biodiversity decline in Southeast Asia (which has previously been among the highest globally) is projected to slow down. Our results suggest that environmentally sustainable land‐use planning alone might not be sufficient to prevent potentially dramatic biodiversity loss, unless a stabilization of climate to pre‐industrial times is observed.

Infection of canola pods by Leptosphaeria maculans and subsequent seed contamination - Angela P. Van de Wouw; Vicki L. Elliott; Andrew Ware; Kurt Lindbeck; Barbara J. Howlett; Steve J. Marcroft (European Journal of Plant Pathology, 2016)

Characterization of Endocarp Biomass and Extracted Lignin Using Pyrolysis and Spectroscopic Methods - Anne E. Harman-Ware; Mark Crocker; Robert B. Pace; Andrew Placido; Samuel Morton; Seth DeBolt (BioEnergy Research, 2015)

Postnatal exposure to MK801 induces selective changes in GAD67 or parvalbumin - Christopher Paul Turner; Danielle DeBenedetto; Emily Ware; Robert Stowe; Andrew Lee; John Swanson; Caroline Walburg; Alexandra Lambert; Melissa Lyle; Priyanka Desai; Chun Liu (Experimental Brain Research, 2010)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)